ISLAM VERSUS GENDER EQUALITY: THE REALITY ABOUT THE ISLAMIC PRINCIPLE OF LIDDHAKARI MITHLU HAZZI AL- UNTHAYAYN (TWO FEMALE PORTION IS EQUIVALENT TO A MALE PORTION, 2:1) IN THE DISTRIBUTION OF A DECEASED’S ESTATES - Magaji Chiroma; Umar Suleiman Abbo-Jimeta; Laminu Bukar (European Scientific Journal, ESJ, 2014)
Islam is a religion that always advocates justice, equity and fairness among people. The religion enjoins its followers to render back justice to whom it is due, even if it can conflict with their interest. Jurisprudentially, the concept of justice has been understood as a subjective phenomenon, but that does not in any way negates the objectives of Shari‘ah (maqasid al- Shari‘ah) in terms of ensuring and maintaining justice among people in the society. In fact, Islam is guided by the revealed sources of law that treats all people equally irrespective of their gender, status, affiliation and background. But then, only the knowledgeable people and the men of wisdom can understand the actual meaning and interpretation of Islamic injunctions. One of the glaring issues that have been confusing people in recent times, most especially people from the faiths other than the Islamic faith, is the issue of gender equality from the Islamic perspective. Notably, the Islamic principle of inheritance that apportioned for a male heir a larger portion of inheritance over a female heir; which nowadays has been seen by some people as an obstacle in achieving the international mission on the actualization of gender equality in the world. It is against this backdrop, the paper clarifies the misconception and misunderstanding involved in the Islamic principles of 2:1. Thus, the paper reveals the actual meaning and wisdom behind such principle within the purview of Islamic law of intestate succession.